(untitled) (Research, Society and Development, 2020)
Ulcerative colitis (UC) is a chronic inflammatory bowel disease restricted to the mucosa, characterized by diarrhea and most often accompanied by major bleeding. The usual current treatment, demonstrating low efficacy, thus, the fecal microbiota transplant (FMT) was proposed as a therapy option. Given the above, the objective of this article is to evaluate the effectiveness of TMF for the treatment of active UC. The research was structured by the PICO methodology (Patient, Intervention, Comparison and Result), inclusion and exclusion criteria and assessment of reliability and quality by Jadad and Chochrane tool. The results were favorable regarding the use of FMT for the treatment of mild and moderately active UC, however, the route of administration, the time of treatment and the identification of the microbial profile necessary for the clinical remission of the disease were divergent in some studies. Through the analysis it was possible to conclude that the FMT has potential in order to provide benefits to patients with UC and more research in the area is necessary to define the best type of treatment for each patient.